Penerapan Pembelajaran Model Learning Cycle (Siklus Belajar) untuk Meningkatkan Aktivitas Belajar Siswa Sekolah Menengah Pertama (SMP) - Muhiddin, Palennari; Adnan, . (bionature, 2010)
This was pre experimental design research with the aim to know student learning activity and study result at the implementation of the learned of learning cycle model. The research was done at state ofÂ  Junior High School 24, class VIII4 at odd semester academic year 2009/2010. Research design was pretest and posttest group design. Data's on students learning activity during they study were collected using observation sheet, and study results were acquired by using study's result test. Data's of student activity and study result were analyzed qualitative descriptive and inferential. T test was used to analyzed the differenceÂ  between before and after the learned of learning cycle model. The mean of result study's before and after application of learned of the learning cycle model was 48.00 for the pretest and 65.69 for the posttest, and t student value was 11,11 with P=0.000 at Î± = 0.01. The research's result showed that learning activities during the application of learned of learning cycle model generally increase, and the difference was very significance between student learning result before and after the learned of learning cycle model being applied .